Atorvastatin Affects Interleukin-2 Signaling by Altering the Lipid Raft Enrichment of the Interleukin-2 Receptor β Chain. (1st September 2005) - Goebel, Jens; Logan, Barbara; Forrest, Kathy; Mieczkowski, Alexandra; Roszman, Thomas L.; Wills-Karp, Marsha
Abstract : ABSTRACT: Although the immunomodulatory properties of statins are in part independent of their lipid-lowering effects, cholesterol is a major component of lipid rafts. We therefore studied the effects of atorvastatin (AS) on the raft enrichment of the interleukin-2 receptor (IL-2R) β chain previously described by us and on early IL-2R signaling events in activated human T cells. We found that concomitant AS exposure during a 3-day stimulation with phytohemagglutinin (PHA) attenuates activation-associated events, such as the enhanced surface expression of the raft marker GM-1 and the induced expression of the activation marker CD25 (the IL-2R α chain). In contrast, brief AS treatment after PHA stimulation increased GM-1 surface expression and virtually abolished the selective raft enrichment of the IL-2R β chain. Although this AS-associated increase in GM-1 expression resembled that seen in the presence of the raft-disrupting cholesterol chelator methyl-β-cyclodextrin (MBCD), the two agents had contrasting effects on the tyrosine phosphorylation of the IL-2R β chain by exogenous IL-2: MBCD essentially abolished this event, whereas AS tended to enhance it and shifted its occurrence out of rafts. We conclude that AS affects IL-2R signaling by altering the raft enrichment of the IL-2R β chain and propose that this effect is one mechanism underlying the immunomodulatory properties of statins.